PHY520 : Quality management and industrial safety / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (Universiti Teknologi MARA (UiTM), 2022)
The course will expose the students to basic principles and concepts of quality improvement, assurance, quality management, occupational safety and health. Basic principles of occupational industrial safety and industrial hygiene are explained. Occupational health standards requirement as stipulated in the law and regulations will be briefed in detail. Safety regulation, Safety at work place, Chemical Hazard management, Biological Monitoring, and radiation safety are all discussed.